Trophic Relationships between the Parasitic Plant Species Phelipanche ramosa (L.) and Different Hosts Depending on Host Phenological Stage and Host Growth Rate - Moreau, Delphine; Gibot-Leclerc, Stéphanie; Girardin, Annette; Pointurier, Olivia; Reibel, Carole; Strbik, Florence; Fernández-Aparicio, Mónica; Colbach, Nathalie (Frontiers in Plant Science, 2016)
Phelipanche ramosa (L.) Pomel (branched broomrape) is a holoparasitic plant that reproduces on crops and also on weeds, which contributes to increase the parasite seed bank in fields. This parasite extracts all its nutrients at the host's expense so that host-parasite trophic relationships are crucial to determine host and parasite growth. This study quantified the intensity with which P. ramosa draws assimilates from its host and analyzed whether it varied with host species, host phenological stage and host growth rate. A greenhouse experiment was conducted on three host species: the crop species Brassica napus (L.) (oilseed rape) and two weed species, Capsella bursa-pastoris (L.) Medik. and Geranium dissectum (L.). Plants were grown with or without P. ramosa and under three light levels to modulate host growth rate. The proportion of host biomass loss due to parasitism by P. ramosa differed between host species (at host fructification, biomass loss ranged from 34% to 84%). Brassica napus and C. bursa-pastoris displayed a similar response to P. ramosa, probably because they belong to the same botanical family. The sensitivity to P. ramosa in each host species could be related to the precocity of P. ramosa development on them. Host compartments could be ranked as a function of their sensitivity to parasitism, with the reproductive compartment being the most severely affected, followed by stems and roots. The proportion of biomass allocated to leaves was not reduced by parasitism. The proportion of pathosystem biomass allocated to the parasite depended on host species. It generally increased with host stage progression but was constant across light induced-host growth rate, showing that P. ramosa adapts its growth to host biomass production. The rank order of host species in terms of sink strength differed from that in terms of host sensitivity. Finally, for B. napus, the biomass of individual parasite shoots decreased with increasing their number per host plant, regardless of host growth rate. Results will be incorporated into a mechanistic model in order to analyse the effect of parasitic plant species on weed community assembly and to design new cropping systems for controlling P. ramosa.